KETIDAKLAZIMAN DIKSI DALAM MEMBUAT KOLOKASI LEKSIKAL (TIPE VERB + NOUN DAN TIPE ADJECTIVE + NOUN) - Purwandari, Gigih Ariastuti (Jurnal Ilmiah Lingua Idea, 2018)
Collocation is the combination of two or more verbs precisely, for example the word interested has to be combined with the word into form interested in. Interested in is the precise or appropriate combination. But, some students sometimes combine the word interested with the word with.  Whereas, interested with is not appropriate. This research discusses the inappropriateness of the diction of making lexcical collocation (type Verb + noun and type adjective + noun) in International Business students of Faculty of Economics and Business Universitas Jenderal Soedirman. This research uses qualitative descriptive method. The data were collected by using a collocation test in sentences and short paragraph. Analysis was conducted by counting the inapropriateness of collocation tested to the respondents. The result showed that frequency of inappropriateness of using lexical collocation type adjective + noun were higher than tye verb + noun. Interlingual was the factor influeced of using two types of  lexical collocation. The mother tongueâs influnce determined  their diction of making apprpriate lexical collocation.